Design of a column test bench for the evaluation of alternative absorbent materials in wastewater treatment. Issue 1 (December 2021) - Mayacela, M; Maldonado, L; Morales, F; Peñafiel, R
Abstract: One of the most used processes for wastewater treatment is filtration, still having unknowns related to the new possible absorbent materials which can provide better pollutant removal. This project proposes a column test bench capable of working with different materials, particle diameters (> 0.35mm) and densities and densities with three columns of 1.5 m length and 4 inches of diameter.. To perform this project, the type of reactive material for the filter medium was identified, considering the nominal and critical size of the fine sand (0.35m), as a basis for determining the design of the length, diameter of the and thickness column. The design conditions were taken so that the hydraulic system can function as a slow and rapid filter. The most critical operating conditions were selected, Qmax: 16.72 lpm and Filtration Rate: 19.80 m / h. Under these operating conditions, a hydraulic head loss of 2.77 m was obtained within the sand column. The result of this research is the design of a column test system that can work under different hydraulics conditions and absorbent materials with sizes greater than 0.35 mm, intended for the investigation of wastewater treatment from car washers and the removal of heavy metals. The final cost of building the column test is about 25% of the commercial price system.